A large-scale multicenter study of long-term outcomes after endoscopic resection for submucosal invasive colorectal cancer - Yoda, Yusuke; Ikematsu, Hiroaki; Matsuda, Takahisa; Yamaguchi, Yuichiro; Hotta, Kinichi; Kobayashi, Nozomu; Fujii, Takahiro; Oono, Yasuhiro; Sakamoto, Taku; Nakajima, Takeshi; Takao, Madoka; Shinohara, Tomoaki; Fujimori, Takahiro; Kaneko, Kazuhiro; Saito, Yutaka (Endoscopy, 2013)
Background and study aims: Patients with submucosal invasive colorectal cancer (SM-CRC) treated with endoscopic resection who are at low risk of lymph node metastasis and local recurrence may be followed up with observation alone, while additional surgery is recommended for those with high risk features. However, the long-term outcomes that these strategies offer are still unclear. The objective of our study was to retrospectively evaluate the long-term outcomes of patients with SM-CRC managed with endoscopic resection.Patients and methods: We retrospectively analyzed all patients with SM-CRC treated by endoscopic resection at six institutions between 2000 and 2007. SM-CRCs with (i) negative vertical margin, (ii) well or moderately differentiated adenocarcinoma, (iii) absence of lymphovascular invasion, and (iv) invasion depth < 1000 µm were classified as low risk. Patients with SM-CRCs without these characteristics were classified as high risk. Outcomes were assessed by 5-year recurrence-free survival (RFS) and recurrence rate.Results: During the study period, 428 patients with SM-CRC (low risk, 126; high risk, 302) who underwent endoscopic resection as their first treatment were enrolled (median follow-up 61 months). Among the 120 patients with low risk features treated by endoscopic resection alone, the 5-year RFS and recurrence rates were 98 % and 0.8 %, respectively. Of the 302 patients with high risk features, 196 underwent additional surgery and 106 were managed with endoscopic resection alone. For those who underwent additional surgery, the 5-year RFS and recurrence rates were 97 % and 3.6 %, respectively. Among the 106 patients managed with endoscopic resection alone, RFS and recurrence rates were 89 % (P < 0.05 vs. low risk patients treated by endoscopic resection alone) and 6.6 % (P < 0.05), respectively. Conclusions: Endoscopic resection alone is adequate for the management of patients with SM-CRC and low risk features. However, in those patients with SM-CRC and high risk features, surgery should be considered in addition to endoscopic resection.